Comparison of nonlinear models in the description of carbon mineralization in litter soil - Silva, Edilson Marcelino; Fruhauf, Ariana Campos; Jane, Sérgio Alberto; Silva, Édipo Menezes da; Muniz, Joel Augusto; Fernandes, Tales Jesus (Revista Agrogeoambiental, 2021)
Litter is an important source of nutrients for trees and can improve the quality of degraded soils. The objective of this study was to describe the dynamics of carbon mineralization in litter soils using nonlinear models, estimating half-life times. Soil carbon mineralization under three types of forest cover was evaluated: Atlantic forest fragment (capoeira), Acacia auriculiformis trees (acacia), and Mimosa caesalpiniifolia (sabiá) from a reforested area with a history of degradation. Twelve measurements of the mineralized carbon were made up to 222 days after the beginning of the incubation of litter soils. Stanford and Smith, Juma, and Cabrera models were fitted by the least squares method using the Gauss-Newton algorithm in the R software. The Stanford and Smith model was more appropriate in describing all treatments, based on the Akaike Information Criterion, with estimates of half-life for Acácia, Capoeira, and Sabiá soils at 25, 44, and 51 days, respectively. The Stanford and Smith and Juma nonlinear models satisfactorily described the carbon mineralization of soils of all treatments.